The effects of taekwondo practice on physical and cognitive variables in children and adolescents: a systematic review - dos Santos, A. O. B.; dos Santos, L. L.; de Souza Cordeiro, L.; de Catsro, J. B. B. P.; de Souza Vale, R. G. (European Journal of Human Movement, 2022)
Taekwondo can develop social responses, beliefs, values, attitudes, and cognitive experiences due to its characteristics and the diversity of frequency, intensity, time, and type of application. This can facilitate the achievement of results related to physical health and cognition in individuals in the formation phases. Thus, this study aimed to analyze the effects of taekwondo practice on physical and cognitive variables in children and adolescents. This systematic review followed the PRISMA recommendations and was registered in PROSPERO (CRD42021293609). The search was performed in the MEDLINE (via PubMed), Scopus, SPORTDiscus, and Web of Science databases. The search terms were related to the theme taekwondo, school, and students with the keywords grouped in a single Boolean phrase: "taekwondo AND school" OR "taekwondo AND students". Studies that analyzed the effects of taekwondo on health-related variables in children and adolescents of both sexes were included. The risk of bias in experimental and quasi-experimental studies was analyzed using the Cochrane Collaboration tool and the Risk Of Bias In Non-randomized Studies - of Interventions (ROBINS-I) tool, respectively. After using the selection criteria, 8 studies were included. Study interventions consisted of a minimum of 8 weeks and a maximum of 72 weeks. There was a total of 402 participants aged between 6 and 16 years, of which 75% were male. The protocols demonstrated improvement in cognitive performance, strength, flexibility, and balance after taekwondo intervention. We concluded that the practice of taekwondo was able to bring positive responses to physical and cognitive performance in children and adolescents.